1989
DOI: 10.1063/1.457091
|View full text |Cite
|
Sign up to set email alerts
|

The rheology of Brownian suspensions

Abstract: The viscosity of a suspension of spherical Brownian particles is determined by Stokesian dynamics as a function of the Péclet number. Several new aspects concerning the theoretical derivation of the direct contribution of the Brownian motion to the bulk stress are given, along with the results obtained from a simulation of a monolayer. The simulations reproduce the experimental behavior generally observed in dense suspensions, and an explanation of this behavior is given by observing the evolution of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
251
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(268 citation statements)
references
References 28 publications
14
251
0
3
Order By: Relevance
“…Since experiments and simulations give the self-diffusion coefficient [1,27], we will focus our description on the dynamics of a single particle whose reduced distribution function ρ k ( r, t) = m P (N ) δ( r k − r)dΓ N satisfies the continuity equation…”
Section: Shear-induced Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since experiments and simulations give the self-diffusion coefficient [1,27], we will focus our description on the dynamics of a single particle whose reduced distribution function ρ k ( r, t) = m P (N ) δ( r k − r)dΓ N satisfies the continuity equation…”
Section: Shear-induced Diffusionmentioning
confidence: 99%
“…Stokesian dynamics simulations [1,27]. The presence of μ( r, t; φ) and E( r, t; φ) implies that the shear-induced diffusion is mediated by hydrodynamic interactions.…”
Section: A Effective Medium Approximationmentioning
confidence: 99%
“…Typically for certain concentrated suspensions of particles, shear thickening may be observed as an abrupt increase in the viscosity of the suspension at a certain shear rate [2]. The detailed mechanism of this shear-thickening phenomenon is still under debate [1][2][3][4][5][6][7][8][9][10]. For colloidal suspensions, the phenomenon is often attributed to the shear-induced formation of hydrodynamic clusters [3]: in this case, the viscosity increases continuously as a consequence of its dependence on particle configuration [4]; this may be but is not necessarily accompanied by an orderdisorder transition in the particle configuration [5].…”
mentioning
confidence: 99%
“…Fumed silica particles form a very complicated three dimensional cluster network due to the branched structure of the particles, unlike the spherical ones [42], but the additive particles are not shaped like the fumed silica where the additives did not contribute to the interactions between particles. It is known that the elongated or extended networks of the hydro-clusters are more effective in the thickening mechanism than the spherical aggregates [4], [42]. The micro-size additive particles occupy large spaces in the nano-size silica suspensions which stops the clusters from extending.…”
Section: Discussionmentioning
confidence: 99%
“…Distributing the additives in the STFs causes the interstitial additive particles between the silica particles, thereby hindering the formation of hydroclusters. Raghavan et al [42] stated that hydro-clusters forming during thickening are elongated structures not spherical aggregations, while Bossis et al [4] suggested that hydrodynamic stresses are proportional to the cube of the larger dimension of the clusters, which means that elongated clusters contribute much more to the thickening behavior than spherical ones. Moreover, the additive particles restrict the hydroclusters from extending during thickening, so they are much smaller in size.…”
Section: Effects On Thickening Periodmentioning
confidence: 99%